2019
DOI: 10.1002/jbmr.3757
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Osteoporosis in China, a Nationwide, Multicenter DXA Survey

Abstract: A number of studies investigated the distribution of BMD values and the prevalence of osteoporosis in China, but their findings varied. Until now, a BMD reference database based on uniform measurements in a large-scale Chinese population has been lacking. A total of 75,321 Chinese adults aged 20 years and older were recruited from seven centers between 2008 and 2018. BMD values at the lumbar spine (L 1 -L 4 ), femoral neck, and total femur were measured by GE Lunar dual-energy X-ray absorptiometry systems. BMD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
206
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 246 publications
(214 citation statements)
references
References 27 publications
(59 reference statements)
7
206
1
Order By: Relevance
“…As the world's most populous country, China is facing an unprecedented rate of growth in the elderly. A recent survey including 75,321 adults reported the age-standardized prevalence of osteoporosis was 6.46 and 29.13% for men and women in the elderly [3]. The number of osteoporosis fractures annually will increase to 5.99 million, and the healthcare cost is predicted to be approximately 25.43 billion dollars by 2050 [4].…”
Section: Introductionmentioning
confidence: 99%
“…As the world's most populous country, China is facing an unprecedented rate of growth in the elderly. A recent survey including 75,321 adults reported the age-standardized prevalence of osteoporosis was 6.46 and 29.13% for men and women in the elderly [3]. The number of osteoporosis fractures annually will increase to 5.99 million, and the healthcare cost is predicted to be approximately 25.43 billion dollars by 2050 [4].…”
Section: Introductionmentioning
confidence: 99%
“…Osteoporosis is a systemic skeletal condition of low bone mass resulting in micro-architectural deterioration of bone tissue, leaving the bones brittle and prone to fractures (1). According to the latest nationwide, multicenter survey in China, a total of 60 million individuals (10.9 million men and 49.3 million women) are estimated to have osteoporosis (2). Based on years of life lost, research revealed that stroke and ischemic heart disease are the leading causes of death and disability at the national level in China (3).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies reported a high prevalence of osteoporosis in postmenopausal women [11,15,16]. The prevalence of osteoporosis in China was reported as 6.46% and 29.13% for men and women aged 50 years and older [17]. Due to the increase of proportion of the elderly population, osteoporosis and osteoporotic fractures have become global health issues of major concern [18,19].…”
Section: Introductionmentioning
confidence: 99%